PENGARUH CORPORATE GOVERNANCE, LEVERAGE DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN NON-KEUANGAN - NURHAIYANI NURHAIYANI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2018)
The purpose of this study is to determine and examine the effect of corporate governance (audit committee, size of the commissioner’s board, and proportion of independent commissioner’s board), firm size, leverage, company growth, profitability, and dividend policy on firm value in non-financial companies listed in Indonesia Stock Exchange. This research used 76 non-financial companies listed in Indonesia Stock Exchange from the period 2013 until 2016 that were selected by using purposive sampling method. The data were analysed by using multiple linear regressions. The research results show that the proportion of independent commissioner’s board, firm size, and profitability had effect towards firm value whereas the audit committee, size of the commissioner’s board, leverage, company growth, and dividend policy had no effect towards firm value.